Isolation and Identification of Salmonella Spp. on Broiler Meat at Banyuwangi and Blambangan Traditional Markets, Banyuwangi Regency - Putri, Diana Novita; Rahmahani, Jola; Yunita, Maya Nurwartanti (Jurnal Medik Veteriner, 2022)
Salmonella spp. is one of the major causes of the world's foodborne disease that can spread through meats, eggs, or milk. Salmonella spp. is an enteropathogenic bacteria that can cause gastrointestinal infections. This study aimed to identify the contaminations of Salmonella spp. bacteria on the broiler meats at Banyuwangi and Blambangan traditional markets Banyuwangi district. The method of this study used 24 samples of broiler meat bought from Banyuwangi and Blambangan traditional markets in the Banyuwangi District. The samples were collected using the purposive sampling method. The results found that 5 out of 24 samples (21%) were tested positive for Salmonella spp. contamination and 19 were tested negative. This study was indicated that broiler meats at Banyuwangi and Blambangan traditional markets Banyuwangi district have not suitable with SNI (Indonesia's National Standard) 3924:2009 that requires at least 25 gram of fresh chicken meat to be free of or tested negative for Salmonella.